Condom equals developmentn ; Pitfall ; Weaver of songs [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Tackles government program on birth and population control; Marcopper's mine tailings disposal into Calancan Bay in Marinduque; and an interview with Susan about her songs on the realities of poverty and exploitation.